- - دکتر عزت الله ملا ابراهیمی (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2001)
Periodicals play an impotant role in the growth and development orpuplic ideas and opinions. They can provide a wast area for the survey of poletical, social and econemic problems in the societies. Palestinians has been strugling with great power during their long life history. But journalists sUivive their courage and bravery through records of the events and happening. This SU/1Jey is a qualitative and quantitaive analysis of the form. and content of Palestinian peliodicals during the Ottoman era.